2011
DOI: 10.2527/jas.2010-3051
|View full text |Cite
|
Sign up to set email alerts
|

Rumen temperature change monitored with remote rumen temperature boluses after challenges with bovine viral diarrhea virus and Mannheimia haemolytica12

Abstract: Remote rumen temperature monitoring is a potential method for early disease detection in beef cattle. This experiment was conducted to determine if remotely monitored rumen temperature boluses could detect a temperature change in steers exposed to bovine viral diarrhea virus (BVDV) and challenged with a common bovine respiratory disease pathogen, Mannheimia haemolytica (MH). Twenty-four Angus crossbred steers (BW = 313 ± 31 kg) were allotted to 1 of 4 treatments: 1) no challenge (control); 2) challenge by a 72… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
52
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(58 citation statements)
references
References 29 publications
4
52
0
2
Order By: Relevance
“…Rumen boluses have also been sold to measure temperature only, these are considerably cheaper than pH sensors but do suffer from a lack of models as to how data can be used. Rose-Dye et al (2011) showed that temperature boluses detected infection challenge in steers.…”
Section: Metabolic Disorders: Rumen Sensingmentioning
confidence: 99%
See 1 more Smart Citation
“…Rumen boluses have also been sold to measure temperature only, these are considerably cheaper than pH sensors but do suffer from a lack of models as to how data can be used. Rose-Dye et al (2011) showed that temperature boluses detected infection challenge in steers.…”
Section: Metabolic Disorders: Rumen Sensingmentioning
confidence: 99%
“…Rumen boluses have also been sold to measure temperature only, these are considerably cheaper than pH sensors but do suffer from a lack of models as to how data can be used. Rose-Dye et al (2011) showed that temperature boluses detected infection challenge in steers.Metabolic disorders: weight and body condition As lactation progresses the BCS changes along with the weight of the cow first falling then rising. Auto-weighing is offered by a number of manufacturers as a standard accessory for milking parlour exits and walk through passages linked to EID.…”
mentioning
confidence: 99%
“…2011; Rose‐Dye et al . 2011). In addition, the ruminal temperature exceeds rectal temperature presumably due to accelerated microbial fermentation (AlZahal et al .…”
Section: Relations Between Ph and Temperature Vfa In Ruminal Fluidmentioning
confidence: 99%
“…A negative correlation has been observed between ruminal pH and ruminal temperature in cows with SARA. Rumen temperature boluses appear to have potential as a tool for detecting temperature changes associated with adverse health events such as exposure to bovine respiratory disease and BVDV (Rose-Dye et al 2014). The ruminal temperature decreased the day before parturition and increased at estrus in spring-calving beef cows, and has a potential use as a predictor of parturition and estrus (Cooper-Prado et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Unlike the telemetric system, the conventional system requires cow cannulation; therefore, the current study provided a non-invasive alternative for measuring ruminal temperature and the prediction of Reticulorumen pH (RpH). Remote rumen temperature monitoring is a potential method for early disease detection in beef cattle (Rose-Dye et al 2014). Radiotelemetry has the potential to improve the detection of SARA and fever on farms (Alzahal et al 2011).…”
Section: Introductionmentioning
confidence: 99%